2013
DOI: 10.1002/brb3.152
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of astrocyte and microglia in supporting oligodendrocyte development and myelination in vitro

Abstract: Oligodendrocyte (OL) development relies on many extracellular cues, most of which are secreted cytokines from neighboring neural cells. Although it is generally accepted that both astrocytes and microglia are beneficial for OL development, there is a lack of understanding regarding whether astrocytes and microglia play similar or distinct roles. The current study examined the effects of astrocytes and microglia on OL developmental phenotypes including cell survival, proliferation, differentiation, and myelinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 41 publications
2
61
0
3
Order By: Relevance
“…Increasing evidences indicated that astrocytes play critical roles in OPCs and OLs survival, maturity and myelination through the intercellular crosstalk (Fischer et al 2014;Pang et al 2013;Stoffels et al 2015;Su et al 2011). The heterogeneous phenotypes of astrocytes are shown to relevantly affect the myelination capacity.…”
Section: Crosstalk Between Astrocytes and Oligodendrocyte Lineage Cellsmentioning
confidence: 97%
“…Increasing evidences indicated that astrocytes play critical roles in OPCs and OLs survival, maturity and myelination through the intercellular crosstalk (Fischer et al 2014;Pang et al 2013;Stoffels et al 2015;Su et al 2011). The heterogeneous phenotypes of astrocytes are shown to relevantly affect the myelination capacity.…”
Section: Crosstalk Between Astrocytes and Oligodendrocyte Lineage Cellsmentioning
confidence: 97%
“…At day 15, we observed OPC-like cells with a bipolar morphology (Figure 2A-D) and the iOPCs could proliferate in response to PDGF-AB and bFGF (Pang et al, 2013) from groups with viral infection. Cells from the four groups were stained for PDGFRα.…”
Section: Combination Of Sox10 and Olig2 Is Better Than Either Factor mentioning
confidence: 94%
“…The results showed that the proportion of PDGFRα + cells from Sox10+Olig2 group was more than that of single factor groups, which was further higher than that of negative control group ( Figure 2E-H, M). To investigate the differential capacity of iOPCs, cells were exposed to differential condition containing T3, NT3, IGF-1 (known to be beneficial for oligodendrocyte differentiation or survival) (Douvaras and Fossati, 2015;Najm et al, 2013;Pang et al, 2013). Cells were stained with O4 antibodies (Douvaras and Fossati, 2015;Pang et al, 2013;Yang et al, 2013) every other week to test whether induced oligodendrocytes (iOLs) had appeared.…”
Section: Combination Of Sox10 and Olig2 Is Better Than Either Factor mentioning
confidence: 99%
See 1 more Smart Citation
“…However, galectin-1 attenuates the loss of myelin and neurodegeneration in animal models for MS [107]. Interestingly, non-reactive microglia and astrocytes influence NG2 glia differently [108]. Astrocyte-derived medium, which consists of increased PDGF-AA, FGF2, CNTF, and growth hormones, promotes proliferation of NG2 glia while microglia-derived medium, consisting more of IGF-1, CX3CL1, IL-2, and IL-5, promotes the differentiation of NG2 glia, indicating different fundamental roles in regulating the fate of oligodendroglia [100].…”
Section: Oligodendrocyte and Ng2 Glia Physiology In The Brainmentioning
confidence: 99%